Assessment of students´ affective-motivational self-regulatory strategies: The EEMA-VS - Suárez Riveiro, José Manuel; Fernández, Ana Patricia (Anales de Psicología / Annals of Psychology, 2011)
This article reports the study of the learning motivational strategies scales–secondary version (EEMA-VS) as an instrument to assess the use of different types of affective-motivational self-regulatory strategies, based on a self-regulatory perspective on student motivation and learning in secon-dary school. The instrument is comprised of three scales: expectancy, value and af-fect. Expectancy scale includes self-concept/self-esteem and expectan-cies/attributions subscales. Value scale includes interest/value and goal generation subscales. Finally, affect scale includes an unique subscale. The results suggest that the EEMA-VS have relatively good reliability. The scales seem to be valid given the results of the three exploratory and confirmatory factor analyses. Use of these strategies is examined.